Vector competence of Aedes aegypti from Havana, Cuba, for dengue virus type 1, chikungunya, and Zika viruses. - Gladys Gutiérrez-Bugallo; Antoine Boullis; Yanet Martinez; Lyza Hery; Magdalena Rodríguez; Juan A Bisset; Anubis Vega-Rúa (Public Library of Science (PLoS), 2020)
Background Like many countries from the Americas, Cuba is threatened by Aedes aegypti-associated arboviruses such as dengue (DENV), Zika (ZIKV), and chikungunya (CHIKV) viruses. Curiously, when CHIKV was actively circulating in the region in 2013-2014, no autochthonous transmission of this virus was detected in Havana, Cuba, despite the importation of chikungunya cases into this city. To investigate if the transmission ability of local mosquito populations could explain this epidemiological scenario, we evaluated for the first time the vector competence of two Ae. aegypti populations (Pasteur and Párraga) collected from Havana for dengue virus type 1 (DENV-1), CHIKV, and ZIKV. Methodology/principal findings Mosquito populations were fed separately using blood containing ZIKV, DENV-1, or CHIKV. Infection, dissemination, and transmission rates, were estimated at 3 (exclusively for CHIKV), 7, and 14 days post exposure (dpe) for each Ae. aegypti population-virus combination. Both mosquito populations were susceptible to DENV-1 and ZIKV, with viral infection and dissemination rates ranging from 24-97% and 6-67% respectively. In addition, CHIKV disseminated in both populations and was subsequently transmitted. Transmission rates were low (<30%) regardless of the mosquito population/virus combination and no ZIKV was detected in saliva of females from the Pasteur population at any dpe. Conclusions/significance Our study demonstrated the ability of Ae. aegypti from Cuba to transmit DENV, ZIKV, and CHIKV. These results, along with the widespread distribution and high abundance of this species in the urban settings throughout the island, highlight the importance of Ae. aegypti control and arbovirus surveillance to prevent future outbreaks.